Gram-positive cell walls stimulate synthesis of tumor necrosis factor alpha and interleukin-6 by human monocytes. - Heumann, D (1994)
Purified cell walls representing a wide variety in teichoic acid and peptidoglycan structure prepared from eight different gram-positive bacterial species induced the production of tumor necrosis factor alpha (TNF-alpha) and interleukin-6 from human monocytes in the presence of 10% plasma or serum. Significant amounts of cytokines began to be produced at concentrations above 100 ng to 1 microgram of cell walls per ml, with maximal production requiring 10 to 100 micrograms of cell wall material per ml. In the absence of plasma, the cytokine-inducing capacity of cell wall preparations was lower by at least an order of magnitude. The serum-derived cofactor was inactivated by heating at 90 degrees C for 30 min, suggesting that the activity is associated with a protein. On the other hand, replacement of normal with hypogammaglobulinemic plasma, inactivation of complement (at 56 degrees C), and blockade by the monoclonal antibody MY4 of the CD14 receptors on monocytes did not inhibit the production of TNF-alpha induced by whole cell walls. Cell walls also stimulated production of TNF-alpha induced by whole cell walls. Cell walls also stimulated production of TNF-alpha in the presence of polymyxin B, and macrophages derived from the lipopolysaccharide-insensitive cell line of C3He/HeJ mice also produced this cytokine when stimulated by cell walls. Both peptidoglycan and the soluble glycan-teichoic acid component prepared by an enzymatic method from the same wall preparation exhibited a serum-dependent induction of TNF-alpha from monocytes, while stem peptides and disacharride peptides had only poor, if any, activity. Cell walls may contribute to the septic shock induced by gram-positive bacteria.